Exploration of Potential Biomarker Genes and Pathways in Kawasaki Disease: An Integrated in-Silico Approach - Srivastava, Priyanka; Bamba, Chitra; Pilania, Rakesh Kumar; Kumari, Anu; Kumrah, Rajni; Sil, Archan; Singh, Surjit (Frontiers in Genetics, 2022)
Kawasaki disease (KD) is a common childhood systemic vasculitis with special predilection to coronary arteries. Even after more than 5 decades of initial description of the disease, etiology of KD remains an enigma. This transcriptome data re-analysis study aimed to elucidate the underlying pathogenesis of KD using bioinformatic approach to identify differentially expressed genes (DEGs) to delineate common pathways involved in KD. Array datasets from Gene Expression Omnibus database were extracted and subjected to comparative meta-analysis for identification of prominent DEGs. Fifteen hub genes with high connectivity were selected from these DEGs (IL1B, ITGAM, TLR2, CXCL8, SPI1, S100A12, MMP9, PRF1, TLR8, TREM1, CD44, UBB, FCER1G, IL7R, FCGR1A). Of these 15 genes, 5 genes (CXCL8, FCGR1A, IL1B, TLR2, TLR8) were found to be involved in neutrophil degranulation. To gain further insight into the molecular mechanism, protein-protein network was established. Significantly enriched pathways based on the above-mentioned genes were mainly centred on biological regulation and signalling events. Additionally, the pathway analysis also indicated that majority of the DEGs in KD were enriched in systemic lupus erythematosus, suggesting a strong interplay between immunological and genetic factors in pathogenesis of KD. These findings could significantly aid in identifying therapeutic targets and understanding KD biosignatures to design a biomarker panel for early diagnosis as well as severity of the disease.